AGAMA DAN MEDIA: PEMAKNAAN ISU AGAMA DI ‘DETIKNEWS’ - Lukas S. Ispandriamo (Millah: Journal of Religious Studies, 2013)
Media has a significant role in strengthening Indonesia's democracy but problematic in writing religions issues. More people are respecting media credibility rather than political branch of power such as parliament, executive or legislative institutions. In the mids of media popularity, it is important to scrutinize online media performance because of its tendency, as well as television media, to focus on selling news for profit. Religious issue has been written more on its sensationality rather than meaningfully. Seven stories of Detiknews were observed of its title, key words and discussion based on journalism perspective. The study shows that Detiknews preferred to write sensational titles, immediacy and less accuracy.